2011
DOI: 10.1016/j.ijrobp.2010.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Local Therapy for Rhabdomyosarcoma of the Hands and Feet: Is Amputation Necessary? A Report From the Children's Oncology Group

Abstract: Purpose To evaluate the outcome of children with rhabdomyosarcoma (RMS) of the hand or foot treated with surgery and/or local radiotherapy (RT). Methods Forty-eight patients with non-metastatic RMS of the hand or foot were enrolled on Intergroup Rhabdomyosarcoma Study Group III, IV-Pilot, and IV. Patients received multi-agent chemotherapy with surgery and/or RT. Twenty-four patients (50%) underwent surgery without local RT, of whom 4 had complete resection and 20 had an amputation. The remaining 24 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In addition, future phase III studies will incorporate standard requirements for lymph node evaluation, since regional lymph node involvement is associated with outcome in ARMS [114] and is an important site of relapse [115]. Phase III studies will include local treatment pathways that maximize local control and minimize morbidity [116][117][118][119][120].…”
Section: Key Trials To Be Pursuedmentioning
confidence: 99%
“…In addition, future phase III studies will incorporate standard requirements for lymph node evaluation, since regional lymph node involvement is associated with outcome in ARMS [114] and is an important site of relapse [115]. Phase III studies will include local treatment pathways that maximize local control and minimize morbidity [116][117][118][119][120].…”
Section: Key Trials To Be Pursuedmentioning
confidence: 99%
“…Studies have tried to explore the associations of age with patient survival and have shown shorter median survival 11 , lower long-term survival probabilities and worse overall/cause-specific/failure-free/event-free survival 8,9,[12][13][14][15] in older patients. Furthermore, Archer 16 concluded that young children tend to have an increased incidence of second malignant neoplasms (SMNs), potentially as a result of a lower chance of death from RMS before developing SMNs and a longer survival time in which to develop SMN.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, with modern surgical techniques, combined with chemotherapy and radiation, 70-80% of patients achieve local control [ 76 , 77 ]. There is some evidence that primary radiotherapy to treat tumors in the hands and feet, where surgery would be severely disfi guring, is as effi cacious as surgery [ 78 ]. All patients are offered chemotherapy, as the tumor is assumed to be metastatic at presentation.…”
Section: 2mentioning
confidence: 99%